Cardiopulmonary resuscitation and endotracheal intubation decisions for adults with advance care directive and resuscitation plans in the emergency department. (December 2020) - Osman, Abdi D.; Rahman, Muhammad Aziz; Lam, Louisa; Lin, Chien-Che; Yeoh, Michael; Judkins, Simon; Pratten, Neely; Moran, Juli; Jones, Daryl
Abstract: Background: Emergency departments routinely offer cardiopulmonary resuscitation and endotracheal intubation to patients in resuscitative states. With increasing longevity and prevalence of chronic conditions in Australia, there has been growing need to uptake and implement advance care directives and resuscitation plans. This study investigates the frequency of the presence of advance care directives and resuscitation plans and its utilisation in cardiopulmonary and endotracheal intubation decision making. Methods: Retrospective audit of electronic patients' medical records aged ≥65 years presenting over a 3-month period. Data collected included demographics, triage categories, advance care directive and/or resuscitation plans/orders status. Results: A total of 6439 patients were included representing 29% of the total patient population during the study period. Participants were randomly selected (N = 300); mean age was 78.7 (±8.1) years. An advance care directive was present in only 8% and one in three patients (37%) had a previous resuscitation plan/order. Senior consultant was present at the department for consultation by junior doctors for most of the patients (82%). Acknowledgment of either advance care directive or resuscitation plans/orders in clinical notes was only 9.5% (n = 116). Conclusion: Advance care directive prevalence was low with resuscitation plans/orders being more common. However, clinician acknowledgement was infrequent for both.